If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 2u + 3 Reorder the terms: 13 = 3 + 2u Solving 13 = 3 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. 13 + -2u = 3 + 2u + -2u Combine like terms: 2u + -2u = 0 13 + -2u = 3 + 0 13 + -2u = 3 Add '-13' to each side of the equation. 13 + -13 + -2u = 3 + -13 Combine like terms: 13 + -13 = 0 0 + -2u = 3 + -13 -2u = 3 + -13 Combine like terms: 3 + -13 = -10 -2u = -10 Divide each side by '-2'. u = 5 Simplifying u = 5
| h/8-1=2 | | 32x+6= | | -7(-2v-8)=6(v+4) | | -9x+1=145 | | 8u+7=95 | | -5/7y-3=x | | q/8--40=50 | | -1/3x-3=y | | 165=g-695 | | x+y+130=0 | | y/8-26=-18 | | 6x+y=3x-2y | | 3x-3=-2(x+1)+4(2-x) | | 3x=11/6 | | 32=2y-7 | | -23=r/-11 | | w/9=13 | | 51=4x-x | | -6(p-6)=36-6p | | g(x)=4x^2+2x-12 | | q/9--34=36 | | 26q=-650 | | -8u+7=-73 | | u+307=927 | | -14+8n=-2+2(4n-6) | | -2n-4=-24 | | (8+7)+(9-2)=18 | | 6r+9=6(r+1)+3 | | v/-28=-31 | | 4x-4=4+X+3 | | 12+x=15-12x | | 10r+5=35 |